The Role of Digital Identification for Healthcare : The Emerging Use Cases - World Bank (World Bank, Washington, DC, 2019)
Identification is crucial for the efficient and effective delivery of health services and public health management and is therefore instrumental for achieving sustainable development goal (SDG). Providers need to know a patient’s identity to access relevant medical and treatment histories and ensure that they are giving consistent and appropriate care. Patients also need documentation to prove enrollment in insurance programs or other safety nets that cover medical expenses. As an alternative to creating a health-specific functional identification system, some countries have instead opted to use existing foundational identification systems, such as population registers, unique identification numbers (UINs) or national ID (NID) cards, as the basis for patient identification, verification, and authentication. The goal of this paper is therefore to synthesize selected examples of how foundational systems are used for healthcare in a variety of countries. The authors hope that this initial effort at framing the utility of foundational identification for healthcare and providing early lessons and key considerations will help guide future work in this area by practitioners, donors, and researchers. This paper is organized as follows: section one gives introduction. Section two provides an overview of the main areas in which using a foundational system is likely to impact healthcare. Section three illustrates the impact areas using country cases from Botswana, Estonia, India, Korea, and Thailand. In light of these examples, section four discusses the key issues for practitioners to consider when integrating foundational identification into health care systems, including high-level design issues and strategies for maintaining data privacy and security. Section five provides concluding thoughts.